Hegemony, morality and emotions - Jeretič, Sebastjan (Teorija in praksa, 2023)
The current debate on the crisis of democracy needs firm epistemological premises for the interpretation of election results and the manifestation of power as consent. In the article, a biopsychosocial model of hegemony is presented as a tool for the manifestation of power in the human mind. Hegemony as conceptualised by Gramsci is developed with the concept of power as both repression or spontaneous generation, as proposed by Foucault. The concept is developed with the paradigm of the embodied mind and insights from psychology and neuroscience about memory formation and meaning creation, stressing the role played by emotions in the process.
Keywords: biopsihosocialni model; biopsychosocial model; Čustva; embodied mind; mental representations; mentalne reprezentacije; Morala; Nadvlada; utelešen um; Volitve